Mortality of marine mussels Mytilus edulis and M. galloprovincialis: systematic literature review of risk factors and recommendations for future research. (6th August 2020) - Lupo, Coralie; Bougeard, Stéphanie; Le Bihan, Véronique; Blin, Jean Louis; Allain, Gwenhael; Azéma, Patrick; Benoit, Fabienne; Béchemin, Christian; Bernard, Ismaël; Blachier, Philippe; Brieau, Léa; Danion, Morgane; et al.
Abstract: The aim of this study was to summarise the literature reporting the risk factors for mortality in the mussel species Mytilus edulis and Mytilus galloprovincialis in order to identify potential science‐based solutions to prevent or mitigate mussel mortality outbreaks. We followed the PRISMA methodology: Preferred Reporting Items for Systematic Reviews and Meta‐Analyses. The studied corpus of 91 publications (114 studies) was highly heterogeneous with respect to the methodological approaches used to define or estimate mussel mortality and the related putative risk factors. Results showed that the mortality risk of both mussel species M. edulis and M. galloprovincialis varied across the seasons, increased with an elevated seawater temperature above a thermal threshold of 20 and 24°C, respectively, decreased by protecting mussels from predation, and was associated with the presence of pathogens in M. edulis . For M. galloprovincialis, using mussel spat from the same area where the farming is carried out and farming them together with another mussel species appears to reduce the mortality risk. However, for M. edulis, this could be achieved by using pure crosses and in particular mussel spat having a selected genotype. For wild bed conservation, sand accumulation and anthropogenic sedimentation should be minimised. Our analysis showed that current approaches to this research topic are limited and are unlikely to yield actionable evidence to identify mussel mortality prevention or mitigation strategies. Therefore, recommendations are offered to increase the ability of future eco‐epidemiological research to identify multiple exposures associated with mussel mortality, underpinned by standardised efforts and cooperative initiatives.